2021
DOI: 10.23887/jpbi.v9i2.487
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Strategies in Online Learning During Covid Pandemic

Abstract: New online teaching strategies had posed many challenges for teachers. It was not easy to be applied, because teachers were still learning E-learning. They encountered some challenges during the implementation. Therefore, teachers used various strategies in online learning to achieve the learning objectives. This research aimed to investigate strategies that teachers used and challenges that they encountered  when they were teaching English during online learning. The research design used in this study was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Meskipun begitu, guru tetap melaksanakan pembelajaran online informatika dengan mempertimbangkan dan menerapkan strategi pembelajaran sesuai dengan berbagai kondisi yang terjadi selama pembelajaran secara online, termasuk kondisi siswa agar siswa tetap belajar di rumah. Sebagaimana pula (Widarini et al, 2021) menjelaskan agar kegiatan belajar mengajar tetap terlaksana meskipun siswa berada di rumah, guru dituntut agar dapat merancang strategi pembelajaran online sebagai inovasi dalam proses pengajarannya. Maka guru diharapkan dapat memilih dan merancang strategi pembelajaran yang tepat dalam pembelajaran secara online guna berinovasi dan mengatasi hambatan-hambatan yang ada dan serta mewujudkan kegiatan belajar mengajar online yang diharapkan…”
Section: Hambatan Yang Dihadapi Guru Dalam Menerapkan Strategi Pembel...unclassified
“…Meskipun begitu, guru tetap melaksanakan pembelajaran online informatika dengan mempertimbangkan dan menerapkan strategi pembelajaran sesuai dengan berbagai kondisi yang terjadi selama pembelajaran secara online, termasuk kondisi siswa agar siswa tetap belajar di rumah. Sebagaimana pula (Widarini et al, 2021) menjelaskan agar kegiatan belajar mengajar tetap terlaksana meskipun siswa berada di rumah, guru dituntut agar dapat merancang strategi pembelajaran online sebagai inovasi dalam proses pengajarannya. Maka guru diharapkan dapat memilih dan merancang strategi pembelajaran yang tepat dalam pembelajaran secara online guna berinovasi dan mengatasi hambatan-hambatan yang ada dan serta mewujudkan kegiatan belajar mengajar online yang diharapkan…”
Section: Hambatan Yang Dihadapi Guru Dalam Menerapkan Strategi Pembel...unclassified
“…During the transitional period, teachers also possible to conduct the learning activity using technology. As the study conducted by previous study showed that in teaching English, teacher use technology such as Google Form, Quizizz, Google Meet, and video (Widarini et al, 2021). Moreover, previous study also reveals about several teaching strategies that in accordance with the I2M3 standard process, and can be implemented in English classes (Azhar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, according to Wena (2009), cooperative learning is a form of group learning that follows a set of laws. The fundamental concept of cooperative learning is that students form small communities and instruct others to accomplish shared goals; clever students can educate students who are not as bright without feeling inferior.…”
Section: Introductionmentioning
confidence: 99%